Role-playing versus Conventional Strategy in Midwifery Clinical Education on Breast Self-examination: A Quasi-Experimental Study - Mahnaz Khatiban (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Iranian women develop breast cancer 10 years earlier than those in developed countries. Breast SelfExamination (BSE) is a useful screening tool. The emphasis on counseling and training is given to promote breast health in the society by midwives. There is a need to educate students with the necessary skills in this area. Aim: To compare the impact of role-playing versus conventional strategy on midwifery student’s skills, and subsequently on their clients' knowledge, skills, and health beliefs about BSE. Materials and Methods: This quasi-experimental study was conducted in two parts. At first, 32 students were equally divided as the role-playing and conventional groups. After educational intervention, the skills of the students in BSE counseling and training were evaluated by a checklist. Then, through convenience sampling, 60 women were equally divided in the experimental and control groups. The experimental group was taught by role-playing group of students and the control group was taught by conventional group of students. The women’s BSE health beliefs, skills, and knowledge were compared before and after education to demonstrate the impact of the students' skills. The women filled out the BSE health beliefs questionnaires. The BSE knowledge questionnaires and the BSE skills checklists were completed by the student through interview and observation respectively. The data were analysed on 5% error using software SPSS-version 16.0. Results: According to the results, the mean score of students' skills in the role-playing group was significantly higher than that of the conventional group (p<0.001) in BSE education and counseling. The results also showed that the women trained by the role-playing group of students had dramatically higher scores (p<0.001) in health beliefs, skills and knowledge about BSE. Conclusion: Role-playing strategy can improve the midwifery student’s counseling and training skills. So, they could be effective in development of women’s knowledge, skills and health beliefs about BSE.